GAPDH, Interferon γ, and Nitric Oxide: Inhibitors of Coronaviruses - Awan, Aashir (Frontiers in Virology, 2021)
As the COVID-19 pandemic finishes its second year, progress has been made against SARS-CoV-2 with vaccine candidates showing efficacy against this latest coronavirus strain. However, this pandemic presents a unique opportunity to investigate anti-viral therapies given the likely probability of another outbreak. One possible (and perhaps unlikely) therapeutic target could be GAPDH (glyceraldehyde-3-phosphate dehydrogenase). Studies have show that downregulation of GAPDH leads to a decrease in interferon gamma (IFNγ production (which is an important cytokine response against coronaviruses and viruses in general). In this light, the previous coronavirus strain (SARS-CoV) has actually been shown to downregulate GAPDH. Although perhaps better known for its role in glycolysis, GAPDH also plays a role in gene expression of a varied set of genes by binding to their mRNA to affect stability and thereby translation Moreover, GAPDH is also upregulated by nitric oxide (NO), an inhibitor against both SARS-CoV and SARS-CoV-2. Additionally, GAPDH has also been shown to be a negative transcriptional regulator of AT1R (angiotensin II receptor 1), which has been shown to bind ACE2 for eventual endocytosis of the complex implicating GAPDH's potential role in the kinetics of coronavirus entry as well in downstream inflammatory signaling resulting from AT1R activation. Lastly, another important role for GAPDH is its requirement in the assembly of the GAIT complex that is responsible for termination of translation of IFNγ-responsive genes that would be critical for the resolution of any inflammatory response. These observations would imply that sufficient levels of GAPDH are needed for immune responses to function properly during a coronaviral infection. By examining different coronavirus studies, this review explores GAPDH's role as an inhibitor of coronaviruses (at the viral transcriptional level and also as a modulator of gene expression related to inflammation), and its signal transduction links to the IFNγ and NO pathways.